Peningkatan Pemahaman Teknologi Kecerdasan Buatan melalui Pelatihan AI Generatif pada SMK AL-MUHAJIRIN Depok - Jiyan Suhada; Hary Setyawan; Kelvin Andrean (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The rapid development of Artificial Intelligence (AI) technology requires an improvement in digital literacy and skills among students, particularly at the vocational high school level. However, many students still lack sufficient understanding of the basic concepts and practical applications of generative AI in learning. This Community Service Program (Pengabdian kepada Masyarakat/PKM) aims to enhance students’ understanding of AI technology through generative AI training at SMK Al-Muhajirin Depok. The methods used in this program include interactive lectures, demonstrations of generative AI applications, and hands-on practice sessions. The activity was attended by 30 students and supported by the school management. The results indicate a significant improvement in students’ understanding of generative AI concepts and their ability to apply the technology in a simple learning context. In addition, students gained awareness of the ethical use of AI in an appropriate and responsible manner. Therefore, this PKM activity contributes positively to improving students’ digital literacy and readiness to face technological advancements in the modern era.